2020
DOI: 10.30918/aerj.82.20.068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of menstruation period on sportive performance of women’s volleyball players

Abstract: The aim of this study was to investigate the effect of some sportive performance on the mensturation of female amateur volleyball players. 15 healthy female athletes with average age 20.0 ± 1.39 years, height average 165.93 ± 5.13 cm, body weight average 57.07 ± 4.42 kg and BMI (body mass index) 20.69 ± 4.78 kg/m 2 , voluntarily partipated in this study. Athletes had training age of 6 years, they participated in regular training, they had regular menstrual cycle for 6 months, and they were not using any regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…and body temperature are influenced by menstrual cycles. In contrast, Guler, et al [7] concluded that menstrual cycles in female futsal players do not affect flexibility, power, speed, anaerobic and aerobic performance. Blanca Romero-Moraleda, et al [8] report that resistance-trained eumenorrhoeic women have similar speed, strength and power performance when exercising with loads equivalent to 20, 40, 60 and 80% of 1RM during the Smith machine half-exercise during exercise in different phases of the menstrual cycle.…”
Section: Vo mentioning
confidence: 92%
“…and body temperature are influenced by menstrual cycles. In contrast, Guler, et al [7] concluded that menstrual cycles in female futsal players do not affect flexibility, power, speed, anaerobic and aerobic performance. Blanca Romero-Moraleda, et al [8] report that resistance-trained eumenorrhoeic women have similar speed, strength and power performance when exercising with loads equivalent to 20, 40, 60 and 80% of 1RM during the Smith machine half-exercise during exercise in different phases of the menstrual cycle.…”
Section: Vo mentioning
confidence: 92%
“…It has been reported that the performances of the athletes in 3 different menstrual cycles did not make a significant difference. In a study conducted by Guler [37] on volleyball players, it was reported that the menstrual cycle did not have any effect on the flexibility, muscle strength, anaerobic power and sprint performances of the athletes. The period of menstruation, physiological changes in body weight, edema in the abdomen, wrists and ankles, pain in the abdomen and waist area, psychological anxiety, irritability, minor depressive states, and mental depressions are clinical symptoms of premenstrual syndrome.…”
Section: Pedagogymentioning
confidence: 95%
“…For instance, 13 of the 25 studies presented in Table 5 assessed muscular strength across the menstrual cycle [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Three of the studies verified menstrual cycle via bloods [ 49 , 54 , 61 ], three via urine [ 55 , 56 , 58 ], one via saliva [ 50 ], one via oral temperature [ 60 ], and five had no menstrual cycle verification protocol [ 51 , 52 , 53 , 57 , 59 ]. Objective verification of the menstrual cycle is important as females without regular ovulatory cycles may reflect a different hormonal profile [ 18 , 62 ].…”
Section: Effects Of the Menstrual Cycle On Sports Performancementioning
confidence: 99%
“…Across the 13 studies assessing muscular strength, different time points in the menstrual cycle were assessed, making comparisons between studies difficult. Three studies evaluated only two phases of the menstrual cycle [ 51 , 54 , 55 ], five evaluated three menstrual cycle phases [ 49 , 52 , 53 , 57 , 58 ], two evaluated four menstrual cycle phases [ 50 , 59 ], two studies evaluated five phases [ 56 , 60 ], and one study evaluated six phases [ 61 ]. There was also variability in the number of cycles assessed; ten studies assessed a single menstrual cycle [ 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 ], two studies assessed two complete menstrual cycles [ 49 , 59 ], and a single study assessed three complete menstrual cycles [ 52 ].…”
Section: Effects Of the Menstrual Cycle On Sports Performancementioning
confidence: 99%
See 1 more Smart Citation